Pembelajaran Tari Persembahan Sedulang Setudung Menggunakan Model Direct Instruction pada Mata Pelajaran Seni Budaya Kelas VIII di MTs Al-Ikhsan Betung - Rizki, Thesya Ramyta; Elvandari, Evita; Firmansyah, Dedy (Indonesian Research Journal on Education, 2023)
This research is a qualitative research with descriptive research method. The data collectiontechniques in this study are observation, interviews, and documentation. Data analysis techniques used in this study are data reduction, data presentation, and conclusions. Based on the results of interviews from the Cultural Arts subject teacher at MTS Al-Ikhsan Betung, Mr. Slamet Riyadi, S.Pd., stated that the students' ability to learn the Sedulang Setudung dance offering was very good, as seen from the enthusiasm and enthusiasm of students in learning activities ranging from theory to practice. This is of course supported by the teacher's ability to choose the right learning model, namely Direct Instruction which plays an important role in achieving student learning outcomes. Based on the results of research on the learning of the Sedulang Setudung dance offering using the direct instruction model in the Class VIII Cultural Arts subject at MTS Al-Ikhsan Betung which wascarried out through 4 learning stages, which included Orientation, Presentation, Practice under the guidance of the teacher, and evaluation which was the final process to determine the level ofunderstanding of students, measuring the level of success of teachers who teach, and knowing theadvantages and disadvantages of the learning model used. 28 students managed to get a scoreabove the predetermined KKM. Of course, it is supported by appropriate learning tools and theselection of the right learning model.